2018
DOI: 10.1108/rjta-02-2018-0017
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-personalization – fashion sustainability through digital clienteling

Abstract: Purpose This study aims to find the model fit to understand the consumer behavior in context to the hyper-personalization through digital clienteling by using structural equation modeling. The traditional method of customer passive observance has been transformed to dominance, where, the fundamental challenge for companies is to understand consumer behavior, work on cost-efficiency and implement sustainable innovation. Design/methodology/approach To investigate this emerging issue, this study aims to find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 15 publications
2
25
0
1
Order By: Relevance
“…The current study is an effort to determine the model fit between conceptual framework and TAM. Though there have been different previous studies where the model fit methods have been used to understand the adaptation of proven theoretical model in the current business scenario (Jain et al, 2018a;Jain et al, 2018b). With the advent of technology, it has been observed that technology is changing spontaneously in the current business scenario.…”
Section: Model Testingmentioning
confidence: 99%
“…The current study is an effort to determine the model fit between conceptual framework and TAM. Though there have been different previous studies where the model fit methods have been used to understand the adaptation of proven theoretical model in the current business scenario (Jain et al, 2018a;Jain et al, 2018b). With the advent of technology, it has been observed that technology is changing spontaneously in the current business scenario.…”
Section: Model Testingmentioning
confidence: 99%
“…[34,124,130,135,139,203,204]. Hyperpersonalization delves into the intricate details and thereby produces much better and effective personalization, which has made it popular in recent times [5,29,146,205,206]. The implementation of this filtering technique with virtual try-on facilities can develop a recommendation system that offers instant image generation of a user wearing the selected fashion item [207,208].…”
Section: Hyperpersonalization Filtering Techniquementioning
confidence: 99%
“…Fashion recommendation systems (FRSs) generally provide specific recommendations to the consumer based on their browsing and previous purchase history. Social-network-based FRSs consider the user's social circle, fashion product attributes, image parsing, fashion trends, and consistency in fashion styles as important factors since they impact upon the user's purchasing decisions [28][29][30][31][32][33][34][35][36][37][38]. FRSs have the ability to reduce transaction costs for consumers and increase revenue for retailers.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, the driving mechanisms for the application of innovative technology appear in innovation support [89] and service intelligence [90]. Regarding innovation support, technologies such as AI, blockchain, cloud computing, big data, and 5G accelerate the formation of cooperative networks among creative enterprises [91], promote the efficient flow of resources [92], accelerate profit acquisition, and attract more creative enterprises to participate in virtual agglomeration.…”
Section: Mechanism Analysismentioning
confidence: 99%